Development of conceptual design and simulation of dapog system rice seed seedling machine for production scale. (May 2019) - Rizaldi, T; Panggabean, S; Ayu, P C; Jeremy, A O
Abstract: Providing a match seeds that could be used to transplanter tray is needed. Therefore the design of an automatic machine that provides rice seedling rolls with better quality and uniformity in a short time, using lower labour amount and fit to the transplanter machine must be conducted. The objective of this research was to design an effective and efficient rice seed dapog system seedling machine for Kubota Transplanter and test through conceptual model simulation. The result showed that the tray must move with a velocity of 10 cm/s (conveyor axis rotation velocity of 13 RPM), the feeder of soil, seeds and cover soil rotation velocity of 8 RPM, 2.5 RPM, and 4 RPM respectively, to create a dapog system rice seed. Simulation test result showed that the movement of each designed component could fulfil the seedling process. Static conceptual model simulation result showed that the highest stress value was 118.77 N/mm 2, maximum deformation was 2.23 mm, and the lowest FoS value was 12.92. Since the occurred stress value was smaller than the maximum stress value of frame material of 745 N/mm 2, it could be concluded that the frame could load the machine.